El proceso de formación docente inicial en el discurso de estudiantes de pedagogía (Educational Perspectives Magazine (REPED), 2023)
An interpretative analysis of the discourse that students of Education produce has revealed that the constitution as subjects of this group of students and their professional training process are influenced by the configuration o f a specifíc psychological and social space. This space is made up of the meanings that the students construct about the training centre. It is in such representations that the students would create their positioning as subjects in the area of social relations of the training centre and probably also in other educational organisations of which they have taken part or will take part in the near fiiture as teachers.
Keywords: Initial Teacher Training, Actors Of The Training Process, Student Voice, Students Of Education, Discourse Analysis.